ANALISIS RANTAI NILAI KOPI PONOROGO - Salikudin, Muhammad (PPPM POLTESA, 2022)
Indonesia currently has four well-known coffee centers such as Nanggroe Aceh Darussalam, North Sumatra, South Sulawesi and East Java, especially in Ponorogo district. Ponorogo regency coffee production currently has a decline from 2012, this is because many damaged crops are attacked by pests. Until now, coffee farmers still treat coffee beans in moderation and their sales are still low, because they are still sold to traditional markets and coffee shops around Ponorogo. So that it allows the value chain that occurs in the production process to sales to consumers. The value chain will later break down the activities into Primary Activities and Support Activities. The purpose of this study is to determine the value cain activity of the value chain Activity which converts input into value added output for consumers. The results of the research on the Ponorogo coffee value chain are that the Ponorogo coffee value chain structure consists of farmers as suppliers, Reog Coffee as manufacturers, and buyers or visitors as consumers, while those who support the Plantation Office and Reog Coffee as post-harvest coffee supervisors. Primary activities include, harvesting fruit and procurement of raw materials as inbound logistics. Red sorting, mininghulling, washing mucus, drying, storing, pulping, roasting, resting, storing and packaging asstages operation.